Women in agriculture: Four myths - Doss, Cheryl; Meinzen-Dick, Ruth S.; Quisumbing, Agnes R.; Theis, Sophie (Elsevier, 2018)
Sustainable Development Goal 5 (SDG) on gender equality and women’s rights and at least 11 of the 17 SDGs require indicators related to gender dynamics. Despite the need for reliable indicators, stylized facts on women, agriculture, and the environment persist. This paper analyzes four gender myths: 1) 70% of the world’s poor are women; 2) Women produce 60 to 80% of the world’s food; 3) Women own 1% of the world’s land; and 4) Women are better stewards of the environment. After reviewing the conceptual and empirical literature, the paper presents the kernel of truth underlying each myth, questions its underlying assumptions and implications, and examines how it hinders us from developing effective food security policies.